Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5539/gjhs.v9n4p76
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Medical Students’ Learning Styles in Terms of Gender

Abstract: Introduction: Every amazing human development in the modern world is resulted from learning; therefore, teaching and learning improvement are the bases of all activities. There is a wide-range of factors affecting learning and the identification of these factors is very important in fixing problems and deficiencies in educational systems. Among the factors contributing to academic achievement are the consideration of students' differences and identification of their learning styles. Accordingly, the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The study pertaining to the prevalence of VL in medical students in Gambia demonstrated quite similar findings as that of our study(Mederos et al, 2019). The study on learning patterns conducted by a group of Iranian researchers demonstrated moreover similar compliance with our study with dominance over VL, however, the results included paramedical samplings apart from medical students(Pour et al, 2017).…”
supporting
confidence: 80%
“…The study pertaining to the prevalence of VL in medical students in Gambia demonstrated quite similar findings as that of our study(Mederos et al, 2019). The study on learning patterns conducted by a group of Iranian researchers demonstrated moreover similar compliance with our study with dominance over VL, however, the results included paramedical samplings apart from medical students(Pour et al, 2017).…”
supporting
confidence: 80%
“…Knowledge of the learning styles of students and the characteristics affecting them is important for teacher to improve lesson plans and develop teaching methodologies to adapt them to their needs. This can also be useful in overcoming the traditional method of the teacher-centered method of teaching. 22 Many factors like learner motivation, study skills, and the ability to assess their own learning needs have been identified as good predictors of student performance, 23 and synchronizing a teaching style with the learning preferences of learners may also bring additional benefits for the learners.…”
Section: Discussionmentioning
confidence: 99%